Definitions of primitive thinking - Duván Ávalos, Édison; Vásquez, Luis Felipe (Boletín Informativo CEI, 2020)
In sociology and anthropology, societies are divided into two groups, according to how they interpret the world around them: a group is formed by civilized or Western societies, employing science, logic and reason to explain natural phenomena. Another group is formed by primitive or savage societies, employing the myths and legends to understand reality.